Chosen but free - Geisler, Norman L. (Minneapolis, Minnesota : Bethany House Publishers, 1999)
Includes bibliographical references.
Keywords: Predestination; Free will and determinism; Providence and government of God; God -- Omniscience; Calvinism; Arminianism